A reminder system for postpartum diabetes screening after gestational diabetes: a randomized clinical trial. (12th December 2022) - Khalifeh, Adeeb; Khosla, Jayasree; Cantor, Eva; Quist-Nelson, Johanna; Saccone, Gabriele; Tumas, Jordyn; Berghella, Vincenzo
Abstract: Objective: To evaluate if a reminder postpartum screening system, providing patients with laboratory requisition on the postpartum ward followed by a telephone reminder one week prior to their 6 weeks appointment, would increase the diabetes mellitus screening rate. Methods: Parallel group, open label, multicenter randomized trial. Patients were recruited between July 2015 and March 2016. All women with gestational diabetes mellitus in their index pregnancy with access to a mobile or landline phone were eligible for participation. Gestational diabetes mellitus diagnosis was made with a one-hour 50 g OGTT ≥135 mg/dl, and a subsequent 3 h OGTT with ≥2 values above fasting 95 mg/dl, 1 h 180 mg/dl, 2 h 155 mg/dl, and 3 h 140 mg/dl. Participants were assigned in a 1:1 ratio to "reminder system" (intervention group) or to "routine care (control group)." Those assigned to the reminder system were provided with two reminders. The first was a laboratory requisition slip given to them while on the postpartum ward. The second was a telephone reminder on the fifth week postpartum, consisting of a standardized script to encourage contacted participants to complete the screening test during the sixth week postpartum. The primary outcome was completion of the two-hour 75 g OGTT 6–12 weeks postpartum. Results: A total of 75 patients were included in the study. Thirty-eight patients were randomized to the reminder system, and 37 patients were randomized to routine care. A total of 22 women (29.3%) completed the test. In the "reminder" group, 31.6% completed the test, and in the "routine care" group 27% of patients completed the test. This increase in screening uptake in the reminder group was not noted to be statistically significant ( p =.8). When evaluating whether perinatal or sociodemographic factors influenced the effect of reminder systems on screening uptake, only insurance type was noted to have a statistically significant influence. Screening uptake was significantly increased in patients with public insurance assigned to "reminder group" (13.5%) compared to those assigned to "routine care" (0%). Of those women who completed the test, seven patients (31.8 %) were diagnosed with prediabetes and none with diabetes. Conclusions: Telephone reminders were not found to have a significant impact on increasing postpartum screening for diabetes. The exception was among the publicly insured population. These findings suggest a targeted role for reminder systems, particularly among those with socioeconomic disadvantage.